RNA Interference-Induced Innate Immunity, Off-Target Effect, or Immune Adjuvant? - Meng, Zhongji; Lu, Mengji (Frontiers in Immunology, 2017)
RNA interference (RNAi) is a natural cellular mechanism that inhibits gene expression in a sequence-specific manner. In the last decade, RNAi has become a cornerstone in basic biological systems research and drug development efforts. The RNAi-based manipulation of mammalian cells facilitates target identification and validation; assists in identifying human disease etiologies; and expedites the development of treatments for infectious diseases, cancer, and other conditions. Several RNAi-based approaches are currently undergoing assessment in phase I and II clinical trials. However, RNAi-associated immune stimulation might act as a hurdle to safe and effective RNAi, particularly in clinical applications. The induction of innate immunity may originate from small interfering RNA (siRNA) sequence-dependent delivery vehicles and even the RNAi process itself. However, in the case of antagonistic cancers and viral infection, immune activation is beneficial; thus, immunostimulatory small interfering RNAs were designed to create bifunctional small molecules with RNAi and immunostimulatory activities. This review summarizes the research studies of RNAi-associated immune stimulation and the approaches for manipulating immunostimulatory activities.